2005
DOI: 10.1001/archinte.165.12.1410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Blood Pressure–Lowering Regimens on Major Cardiovascular Events in Individuals With and Without Diabetes Mellitus

Abstract: These overviews showed that the short- to-medium-term effects on major cardiovascular events of the BP-lowering regimens studied were broadly comparable for patients with and without diabetes. Different effects of regimens on intermediate renal outcomes not evaluated in these overviews may still provide a rationale for using specific drug classes in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(85 citation statements)
references
References 20 publications
2
78
0
1
Order By: Relevance
“…Although increased cardiac expression of RAS components are linked to the pathogenesis of heart disease the outcomes of trials evaluating the efficacy of angiotensin converting enzyme (ACE) inhibitors, Ang II receptor blockers (ARBs) or a direct renin inhibitor have not fully achieved the benefits that would be expected from a robust experimental literature documenting Ang II as a cause of or a major contributor to the pathogenesis of heart disease (Disertori et al, 2012; Laight, 2009; Turnbull et al, 2005; Turnbull et al, 2007; Turnbull et al, 2008). To reconcile the gap between treatment effects in animal experiments and clinical trials results, proposed explanations include species differences in Ang II processing pathways in humans and animals (Balcells et al, 1997; Ferrario et al, 2005b), compensatory ACE inhibition escape (Ennezat et al, 2000; van den Meiracker et al, 1992), failure of drugs to access the intracellular sites at which Ang II acts (Baker et al, 1992; De Mello and Danser, 2000; Dostal and Baker, 1999; Kumar et al, 2012), or these factors in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Although increased cardiac expression of RAS components are linked to the pathogenesis of heart disease the outcomes of trials evaluating the efficacy of angiotensin converting enzyme (ACE) inhibitors, Ang II receptor blockers (ARBs) or a direct renin inhibitor have not fully achieved the benefits that would be expected from a robust experimental literature documenting Ang II as a cause of or a major contributor to the pathogenesis of heart disease (Disertori et al, 2012; Laight, 2009; Turnbull et al, 2005; Turnbull et al, 2007; Turnbull et al, 2008). To reconcile the gap between treatment effects in animal experiments and clinical trials results, proposed explanations include species differences in Ang II processing pathways in humans and animals (Balcells et al, 1997; Ferrario et al, 2005b), compensatory ACE inhibition escape (Ennezat et al, 2000; van den Meiracker et al, 1992), failure of drugs to access the intracellular sites at which Ang II acts (Baker et al, 1992; De Mello and Danser, 2000; Dostal and Baker, 1999; Kumar et al, 2012), or these factors in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Ten treatable risk factors have been associated with 90% of the risk of ischemic or hemorrhagic stroke (O'Donnell et al., 2010). The risk profile for occurrence of MI is quite different than that for stroke (Yusuf et al., 2004), but hypertension is one important risk factor for stroke, MI or vascular cause of death (Carlson & Böttiger, 1985; Conroy et al., 2003; Håheim et al., 1993; Harmsen et al., 1990; Hu et al., 2005; Psaty et al., 2001; Qizilbash, Lewington, Duffy, & Peto, 1995; Seshadri et al., 2006) and antihypertensive treatment(s) reduces these risks (Hackam & Spence, 2007; Hankey, 2014; Mancia et al., 2013; Turnbull, 2003; Turnbull et al., 2005; Wachtell, Hornestam, et al., 2005; Wachtell, Lehto, et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…thiazide diuretics, β-blockers, calcium channel blockers (CCBs), ACEIs and angiotensin receptor blockers (ARBs) [2,9,12,13]. A systematic review pooling the data from 27 randomized trials concluded that the risk of total major cardiovascular events was similarly reduced for patients with and without diabetes receiving BP-lowering regimens based on the five classes of AHDs [14]. However, with few exceptions, studies reported no significant general advantage of one drug over the other for cardiovascular outcomes following antihypertensive therapy in diabetes [2,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review pooling the data from 27 randomized trials concluded that the risk of total major cardiovascular events was similarly reduced for patients with and without diabetes receiving BP-lowering regimens based on the five classes of AHDs [14]. However, with few exceptions, studies reported no significant general advantage of one drug over the other for cardiovascular outcomes following antihypertensive therapy in diabetes [2,12,14]. A more recent review gathering data from clinical trials and literature of BP therapy also concluded that various AHDs had similar effectiveness in reducing coronary artery disease events, but showed a potential to result in worsened metabolic control in patients with diabetes [15].…”
Section: Introductionmentioning
confidence: 99%